The Impact of Cardiovascular Diseases on Cardiovascular Regulation During Exercise in Humans: Studies on Metaboreflex Activation Elicited by the Post-exercise Muscle Ischemia Method - Crisafulli, Antonio (Current Cardiology Reviews, 2017)
Background: Hemodynamics during dynamic exercise is finely regulated by some neural mechanisms. One of these mechanisms is the metabolic part of the exercise pressor reflex, i.e. the muscle metaboreflex. Hemodynamic response during the metaboreflex is characterised by the recruitment of the reserves in cardiac inotropism, pre-load, after-load and chronotropism. If one of these reserves is exhausted, then the cardiovascular response is achieved by recruiting one of the other reserves, thereby indicating a remarkable plasticity of the control of circulation. Conclusion: In this review, the effects of a number of cardiovascular diseases - such as heart failure, heart failure with preserved ejection fraction, hypertension, type 1 and type 2 diabetes mellitus, obesity and metabolic syndrome - on hemodynamics during the metaboreflex are reviewed.
Keywords: Inotropism